2016
DOI: 10.14744/anatoljcardiol.2016.7209
|View full text |Cite
|
Sign up to set email alerts
|

Release of mitochondrial DNA correlates with peak inflammatory cytokines in patients with acute myocardial infarction

Abstract: Objective:The present study is an exploration of the dynamic changes of plasma mitochondrial deoxyribonucleic acid (mtDNA) and inflammatory level in patients with acute myocardial infarction (MI).Methods:Thirty-eight patients with acute MI and 33 control participants were included in the study. Blood samples were collected on admission, 12 hours post-percutaneous coronary intervention (PCI), 24 hours post-PCI, and 48 hours post-PCI. White blood cell (WBC) count and C-reactive protein (CRP) level were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Serum mtDNA of acetaminophen overdose patients with derangement in the liver enzyme alanine aminotransferase (a marker of hepatocyte damage) is significantly higher than that of overdose patients who had normal liver enzymes 27 , suggesting that the extent of mtDNA release into the circulation depends on the extent of hepatocyte necrosis. Similarly, extensive cardiomyocyte necrosis is found in acute myocardial infarction, which is also associated with elevated mtDNA in multiple studies 28 30 and falls after angioplasty or coronary stent insertion to restore blood flow to the damaged myocardium 28 , 29 . Patients with diabetes mellitus and coronary artery disease have higher mtDNA levels than those with diabetes but without coronary artery disease 31 , 32 .…”
Section: Elevated Circulating Mtdna In Human Diseasesmentioning
confidence: 94%
“…Serum mtDNA of acetaminophen overdose patients with derangement in the liver enzyme alanine aminotransferase (a marker of hepatocyte damage) is significantly higher than that of overdose patients who had normal liver enzymes 27 , suggesting that the extent of mtDNA release into the circulation depends on the extent of hepatocyte necrosis. Similarly, extensive cardiomyocyte necrosis is found in acute myocardial infarction, which is also associated with elevated mtDNA in multiple studies 28 30 and falls after angioplasty or coronary stent insertion to restore blood flow to the damaged myocardium 28 , 29 . Patients with diabetes mellitus and coronary artery disease have higher mtDNA levels than those with diabetes but without coronary artery disease 31 , 32 .…”
Section: Elevated Circulating Mtdna In Human Diseasesmentioning
confidence: 94%
“…There is a growing body of literature demonstrating that circulating mtDNA levels are elevated in large variety of human diseases, including sepsis ( 29 36 , 191 , 192 ), trauma, pulmonary embolism ( 193 ), liver failure ( 53 , 54 ), stroke ( 57 ), and cancer ( 45 50 ). Numerous recent clinical studies have suggested that mtDNA circulating level may represent a new biological marker of the severity of tissue injury for critical ill patient admitted with sever sepsis ( 29 36 , 191 , 192 ), trauma ( 13 , 31 , 36 , 39 42 ), myocardial infarction ( 194 , 195 ), and cardiogenic shock ( 44 ) since a correlation between mtDNA levels, injury severity and outcome has frequently been observed ( 30 , 32 , 36 , 39 , 41 , 192 ). Interestingly, Krychtiuk et al ( 30 ) demonstrated not only that mtDNA levels were associated with mortality in critical ill patients but also that TLR9 expression in patients increase the association between mtDNA and mortality.…”
Section: Mitochondrial Damps In Human Diseasesmentioning
confidence: 99%
“…Acute myocardial infarction is accompanied by massive cardiomyocyte necrosis and tissue inflammation. In multiple studies, it was reported that this extensive cardiomyocyte necrosis is also associated with elevated circulating mtDNA levels [ 91 93 ]. In addition, the increased level of mtDNA is reduced after reperfusion of the ischaemic myocardium, suggesting a close relation between myocardial damage and mtDNA [ 91 , 92 ].…”
Section: Mtdna and Cardiac Inflammationmentioning
confidence: 99%